FLASH radiotherapy: Considerations for multibeam and hypofractionation dose delivery. (November 2021) - MacKay, Ranald; Burnet, Neil; Lowe, Matthew; Rothwell, Bethany; Kirkby, Norman; Kirkby, Karen; Hendry, Jolyon
Highlights: Temporal aspects of clinical FLASH delivery. Possible effects of fractionated FLASH dosimetry. Examining the initial clinical applications. Extension of clinical studies required to demonstrate normal tissue sparing.